Optimization of the cooling characteristics in high-voltage LEDs. (2nd June 2016) - Yao, Qi; Shih, Tien-Mo; Chang, Richard Ru-Gin; Chen, Zhong; Gao, Yu-Lin; Lu, Yi-Jun
ABSTRACT: Cooling is a critical process in the thermal designs of high-voltage light-emitting diodes (HV-LEDs), whose junction temperatures are in turn an essential criterion for evaluations of LED aging, light-color quality, and luminous efficacies. In the present work, both numerically and experimentally, we have identified two cooling-related parameters, namely thermal crowdedness and nonuniformity, that are related to the lowering of junction temperatures of 17 microchips. Based on these two parameters, we have further proposed three regimes that facilitate the optimization. In addition, great care must be taken to incorporate the difficulty of tackling the high voltage into electrical-resistance selections. The 3D transient conjugate heat transfer is simulated using the finite element package named COMSOL. Finally, we hope that the present study can provide the photonic and cooling industries with the guidance for optimizing cooling characteristics in HV-LEDs based on these two parameters and three regimes.